2013
DOI: 10.4081/jphia.2013.e5
|View full text |Cite
|
Sign up to set email alerts
|

Is sexual abuse a part of war? A 4-year retrospective study on cases of sexual abuse at the Kenyatta National Hospital, Kenya

Abstract: The harmful effects of sexual abuse are long lasting. Sexual abuse when associated with violence is likely to impact negatively on the life of the victim. Anecdotal reports indicate that there was an increase in the number of cases of sexual violence following the 2007 post election conflict and violence in Kenya. Although such increases in sexual abuse are common during war or conflict periods the above reports have not been confirmed through research evidence. The purpose of the current study is to establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…The prevalence of sexual abuse among children under 18 years of age in Kenya over a period of 5 years (2007–2013) reported that 11.8% of the girls and 3.6% of the boys had been exposed to sexual abuse [ 11 ]. An earlier study during the period 2006–2009 found out that 28.3% of the sexual abuse cases among children assessed and treated at Kenyatta National Hospital (KNH), Nairobi Kenya were young and below 18 years of age [ 12 ]. Psychosocial outcomes associated with sexual abuse included depression [ 13 ], post traumatic-stress disorder (PTSD) and declining school grades among many other negative outcomes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of sexual abuse among children under 18 years of age in Kenya over a period of 5 years (2007–2013) reported that 11.8% of the girls and 3.6% of the boys had been exposed to sexual abuse [ 11 ]. An earlier study during the period 2006–2009 found out that 28.3% of the sexual abuse cases among children assessed and treated at Kenyatta National Hospital (KNH), Nairobi Kenya were young and below 18 years of age [ 12 ]. Psychosocial outcomes associated with sexual abuse included depression [ 13 ], post traumatic-stress disorder (PTSD) and declining school grades among many other negative outcomes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Con relación al no registro de datos sociodemográficos en las historias clínicas, es un hallazgos consistente en otros estudios como el del Curia et al (26) , quienes reportaron su ausencia en una gran proporción, especialmente en lo que respecta a información sobre educación, ocupación, estado civil y edad.…”
Section: Discussionunclassified